2008
DOI: 10.1002/marc.200800071
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Surface Wettability of Poly(3‐sulfopropyl methacrylate) Brushes by Cationic Surfactant‐Driven Interactions

Abstract: In this communication, polyanionic poly(potassium 3‐sulfopropyl methacrylate) (PSPM) brushes were switched from hydrophilic to hydrophobic by exchange of the counter cations. First, poly(potassium 3‐sulfopropyl methacrylate) brushes were grown by means of atom transfer radical polymerization (ATRP) from thiol monolayers of initiating ω‐mercaptoundecyl bromoisobutyrate and mixed monolayers of thiol initiator and 1‐undecanothiol (blank thiol) attached to gold surfaces. The kinetics of the polymerization reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 29 publications
0
32
0
Order By: Relevance
“…The most obvious change in contact angles was observed with PSPMA brush modification, which were all less than 10 , leading to superhydrophilic surfaces. 56 In the XPS spectra (Fig. 7A-C), the strong S 2p peaks appeared at about 168.8 eV but were not detected in the original PI, PTFE, and PDMS, indicating the successful grafting of the PSPMA brushes.…”
Section: Surface-patterning Through Microcontact Printing Of the Macr...mentioning
confidence: 94%
See 1 more Smart Citation
“…The most obvious change in contact angles was observed with PSPMA brush modification, which were all less than 10 , leading to superhydrophilic surfaces. 56 In the XPS spectra (Fig. 7A-C), the strong S 2p peaks appeared at about 168.8 eV but were not detected in the original PI, PTFE, and PDMS, indicating the successful grafting of the PSPMA brushes.…”
Section: Surface-patterning Through Microcontact Printing Of the Macr...mentioning
confidence: 94%
“…7A-C), the strong S 2p peaks appeared at about 168.8 eV but were not detected in the original PI, PTFE, and PDMS, indicating the successful grafting of the PSPMA brushes. 56 Using the same method, we also tried to graft polymer brushes on textile and wood surfaces, which are two useful substrates for daily application. 57 As shown in Fig.…”
Section: Surface-patterning Through Microcontact Printing Of the Macr...mentioning
confidence: 99%
“…Huck's group has investigated sulfopropyl methacrylate brushes containing silver cations [34]. While this Ag + loaded system was effective for preventing bacterial colonization, a subsequent paper showed that the effective silver concentrations were also cytotoxic towards mammalian cells.…”
Section: Charged Non-biofouling Polymer Brushesmentioning
confidence: 98%
“…Then, the sample was immersed in 10 À2 M 1-undecanethiol in EtOH to fill nonpatterned regions. Finally, the samples were rinsed and Surface Polymerization [19] PSPM was synthesized from the gold surfaces patterned with v-mercaptoundecyl bromo-isobutyrate. For the brush polymerization the patterned surface was incubated at 40 8C for 3 h in a dimethylformamide (DMF)/water solution of sulfo propyl methacrylate (SPM)/2,2-bipyridine/CuCl/ CuCl 2.…”
Section: Surface Patterningmentioning
confidence: 99%